Kidney patient struggles - Williams, Jess (Raton Range Raton, New Mexico, 1988)
Newspaper Article on Mildred Hay getting honored at Sunwest Bank for 35 years of service.
Master list item #: 21
File location is in the Raton File Cabinet
Keywords: Floyd, David; Floyd, Alandra; Floyd, Fred; Presbyterian Hospital; Local History; Biography; Life and Customs; Operation; Kidney Transplant; Recovery; Complications